Деятельность правительства и реформы 1922-1926 гг. в Румынии - Піддубний, Ігор (Suceava, Universitatea „Ștefan cel Mare”, 2014)
Acest studiu analizează problema schimbărilor din domeniul legislativ, administrativ, economic, financiar şi educaţional iniţiate de guvern în anii 1922-1926, ce au condus la un anumit grad de unificare instituţională a ţării. De asemenea, atunci a fost accelerat procesul de modernizare a societăţii românești, în manieră occidentală, declanșat în a doua jumătate a secolului XIX. În fond, în acești ani au fost înregistrate cele mai importante succese ale „decadei brătieniste”, termen consacrat încă din perioada regimului comunist în istoriografia română. This study analyses the problem of changes in the legislative, administrative, economic, financial and educational fields, initiated by the government in 1922-1926, which led to a certain degree of institutional unification of the country. Also, in that period has accelerated the modernization of the Romanian society process, in the Western manner, started in the second half of the nineteenth century. Actually, in those years were realized the most important successes of “Brătianu decade”, an expression established since the period of the communist regime in the Romanian historiography. L’étude ci-jointe examine la question des changements dans les domaines législatif, administratif, économique, financier et éducatif initiés par le gouvernement pendant les années 1922-1926, qui conduisirent à un certain degré d'unification institutionnelle du pays. De plus, on accéléra, aussi, le processus de modernisation de la société roumaine, de manière occidentale, démarré dans la seconde moitié du XIX-ème siècle. En effet, ces années-là, on enregistra les plus grands succès de la «décennie des Brătianu», terme qu’on consacra dès la période communiste dans l’historiographie roumaine.
Activities of the Government and the reforms of 1922-1926 in Romania
Les activités du Gouvernement et les réformes des années 1922-1926 en Roumanie
Keywords: I.I.C. Brătianu; the Romanian Government; Constitution; administrative reform; financial system